Genomewide m6A Mapping Uncovers Dynamic Changes in the m6A Epitranscriptome of Cisplatin-Treated Apoptotic HeLa Cells - Azime Akçaöz Alasar; Özge Tüncel; Ayşe Bengisu Gelmez; Buket Sağlam; İpek Erdoğan Vatansever; Bünyamin Akgül (Cells, 2022)
Cisplatin (CP), which is a conventional cancer chemotherapeutic drug, induces apoptosis by modulating a diverse array of gene regulatory mechanisms. However, cisplatin-mediated changes in the m6A methylome are unknown. We employed an m6A miCLIP-seq approach to investigate the effect of m6A methylation marks under cisplatin-mediated apoptotic conditions on HeLa cells. Our high-resolution approach revealed numerous m6A marks on 972 target mRNAs with an enrichment on 132 apoptotic mRNAs. We tracked the fate of differentially methylated candidate mRNAs under METTL3 knockdown and cisplatin treatment conditions. Polysome profile analyses revealed perturbations in the translational efficiency of PMAIP1 and PHLDA1 transcripts. Congruently, PMAIP1 amounts were dependent on METTL3. Additionally, cisplatin-mediated apoptosis was sensitized by METTL3 knockdown. These results suggest that apoptotic pathways are modulated by m6A methylation events and that the METTL3–PMAIP1 axis modulates cisplatin-mediated apoptosis in HeLa cells.